Thermoelectric properties of the layered oxides LnBaCu(Co)FeO₅₊δ(Ln = La, Nd, Sm, Gd) - Klyndyuk, A.I.; Chizhova, Ye.A. (Functional Materials, 2009)
The crystal structure, electrical conductivity and thermo-e.m.f. of layered oxides LnBaCu(Co)FeO₅₊δ(Ln=La, Nd, Sm, Gd) of perovskite structure have been studied. The LnBaCu(Co)FeO₅₊δ compounds have cubic structure for Ln = La and tetragonal one for the Ln = Nd-Gd and are p-type semiconductors (except for LaBaCoFeO₅₊δ having negative S values). The activation energy of electric transport, thermoelectric coefficients (Seebeck, Pel tier and Thomson) and the power factor of the oxides studied have been determined. The power factor of LnBaCu(Co)FeO₅₊δ phases has been found to depend on the nature of rare earth elements and 3d-metals in their structure and to be maximum for SmBaCuFeO₅₊δ, GdBaCuFeO₅₊δ and NdBaCoFeO₅₊δ. The layered perovskites can be considered as a base for development of the new thermoelectric oxide materials.